The lncRNA MEG3/miR‐16‐5p/VGLL4 regulatory axis is involved in etoposide‐induced senescence of tumor cells. (22nd December 2020) - Tao, Ye; Yue, Peipei; Miao, Yongnan; Gao, Shuting; Wang, Biao; Leng, Sean X.; Meng, Xin; Zhang, Haiyan
Abstract: Background: The senescence of tumor cells is an important tumor suppressor mechanism. The present study aimed to investigate the role of long non‐coding RNA (lncRNA) MEG3 (maternally expressed gene 3) in the senescence process of tumor cells and its potential molecular mechanism by competitively binding with microRNA miR‐16‐5p to regulate the expression of VGLL4 (encoding vestigial like family member 4). Methods: We used etoposide to construct senescence models of tumor cells. The degree of cellular senescence was detected by senescence‐associated β‐galactosidase, cell cycle and senescence‐associated secretory phenotype. The expression of lncRNA MEG3, miR‐16‐5p and VGLL4 in senescent or non‐senescent cells was evaluated using a quantitative real‐time reverse transcriptase‐PCR (qRT‐PCR) or western blotting. Dual luciferase reporter assays were used to detect the binding of miR‐16‐5p to lncRNA MEG3 and VGLL4. The mRNA and protein expression levels of senescence‐related markers (p53, p21 and p16) were detected using qRT‐PCR or western blotting. Results: Compared to the control group, the expression of lncRNA MEG3 and VGLL4 was significantly up‐regulated in senescent cells. Knockdown of lncRNA MEG3 and VGLL4 reduced the degree of senescence and the expression of p21 and p16. lncRNA MEG3 interfered with the expression of miR‐16‐5p in senescent A549 and MCF‐7 cells. The expression of VGLL4 was regulated by miR‐16‐5p in senescent A549 and MCF‐7 cells. lncRNA MEG3 participated in the senescent progress of tumor cells induced by etoposide via the miR‐16‐5p/VGLL4 axis. Conclusions: The present study has confirmed the regulatory role of the lncRNA MEG3/miR‐16‐5p/VGLL4 axis in the low‐dose etoposide‐induced tumor cell senescence model, which has potential clinical application with respect to treating malignant tumors. Abstract : Long non‐coding RNA (lncRNA) MEG3 (maternally expressed gene 3) is closely related to the senescence of tumor cells, and its expression level is up‐regulated in senescence and positively correlated with the degree of senescence. In the senescence model of tumor cells, the expression of microRNA miR‐16‐5p is inhibited and participates in senescence through negative regulation of VGLL4 (encoding vestigial like family member 4), whereas the expression of VGLL4 is positively correlated with the expression of lncRNA MEG3. The lncRNA MEG3/miR‐16‐5p/VGLL4 axis is involved in the regulation of senescence of tumor cells, presenting an opportunity for the development of a tumor suppressor mechanism.